Impact of the COVID-19 Pandemic on the Mental Health of College Students: A Systematic Review and Meta-Analysis - Li, Yang; Wang, Aiwen; Wu, Yalin; Han, Nana; Huang, Huiming (Frontiers in Psychology, 2021)
Background The coronavirus disease (COVID-19) pandemic has been spreading and brought unprecedented psychological pressure on people across the entire globe since December 2019. Objectives To synthesize the existing evidence of the prevalence of mental health status during the epidemic and provide the basis for mental health education. Materials and methods The literature search was conducted in nine databases from December 2019 to October 2020. The risk of bias for each study was assessed, and the random-effects meta-analysis was used to estimate the prevalence of specific mental health problems. The review protocol was registered in PROSPERO with the registration number CRD42020208619. Results About 27 studies were included in the analysis with a total of 706,415 participants combined, and 14 mental health problems were gathered. Meta-analysis showed that the prevalence of depression was 39% (95% CI: 27–51%) and that of anxiety was 36% (95% CI: 26–46%). Subgroup analysis indicated that the prevalence of depression and anxiety varied among nations and due to the survey date. The prevalence of depression (60%, 95% CI: 46–74%) and anxiety (60%, 95% CI: 46–74%) in non-Chinese college students was higher than those in Chinese college students (26%, 95% CI: 21–30% and 20%, 95% CI: 14–26%). The proportion of depression (54%, 95% CI: 40–67%) and anxiety (37%, 95% CI: 26–48%) was higher after March 1 than before it (21%, 95% CI: 16–25% and 19%, 95% CI: 13–25%). Conclusions The meta-analysis results presented that the prevalence of depression (39%) or anxiety (36%) among college students greatly increased during the COVID-19 pandemic. In addition, the mental health of college students is affected by the nations and the survey date. It was necessary to take measures to reduce mental health risks during the pandemic.